1990
DOI: 10.1111/j.2042-7158.1990.tb07053.x
|View full text |Cite
|
Sign up to set email alerts
|

AHR-15010—A Novel Anti-arthritic Agent

Abstract: AHR-15010 (3-(2-methoxyphenoxy)-1,2-propanediol bissulphamate ester) is a compound of novel structure that displays anti-arthritic activity in adjuvant arthritis in rats. When given orally from days 18 through day 50, (excluding weekends) after adjuvant injection, AHR-15010, at doses of 3.16 to 100 mg kg-1, produced significant anti-inflammatory activity and reduced the severity of the hind paw joint lesions as monitored by X-ray analysis. AHR-15010, however, has no acute anti-inflammatory activity in the Evan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Among them, bisulfamates such as AHR-15010 65, were reported to possess anti-arthritic activity in adjuvant arthritis rats, acting by an unique mechanism of action. [141][142][143] It was suggested that this mechanism resulted from the inhibitory effect of AHR-15010 on CAs as it was demonstrated that these enzymes (and more specifically, isozyme CA II) are involved in bone resorption [2][3][4][5] (see also Table X, and the discussion on CA inhibitors in this review). The use of CAIs could be a valuable approach for the management of arthritic diseases, but no progress in this field has been registered ultimately.…”
Section: B Sulfamates As Anti-arthritis and Anti-osteoporosis Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Among them, bisulfamates such as AHR-15010 65, were reported to possess anti-arthritic activity in adjuvant arthritis rats, acting by an unique mechanism of action. [141][142][143] It was suggested that this mechanism resulted from the inhibitory effect of AHR-15010 on CAs as it was demonstrated that these enzymes (and more specifically, isozyme CA II) are involved in bone resorption [2][3][4][5] (see also Table X, and the discussion on CA inhibitors in this review). The use of CAIs could be a valuable approach for the management of arthritic diseases, but no progress in this field has been registered ultimately.…”
Section: B Sulfamates As Anti-arthritis and Anti-osteoporosis Agentsmentioning
confidence: 99%
“…The arthritic diseases are systemic inflammatory diseases characterized by considerable damage of connective tissue structures of the joint and adjacent structures leading to progressive cartilage and bone destruction. [141][142][143] Diverse classes of therapeutic agents have been used over the past 40 years to treat arthritis including adrenal corticosteroids and non-steroidal anti-inflammatory drugs. [141][142][143] One of the clinical features of arthritis and also osteoporosis is bone resorption, leading to bone loss.…”
Section: B Sulfamates As Anti-arthritis and Anti-osteoporosis Agentsmentioning
confidence: 99%
See 2 more Smart Citations